Effect of Annealing Temperature of Cugao2 thin Films by Using RF Magnetron Sputtering Technique on Optical and Structural Properties - Yip, Lam Wai; Alias, Afishah; Awang, Asmahani Binti; Rahman, Abu Bakar Bin Abd; Mohamad, Khairul Anuar Bin; Nayan, Nafarizal Bin; Pien, Chee Fuei; Abdullah, Siti Ashraf (International Journal of Engineering and Technology, 2018)
Cu-based conductive oxide such as CuGaO2 is seen to be a promising transparent p-type oxide material. The study of p-type semiconductor CuGaO2 thin films have been carried out to investigate the effects of different parameters in providing the optimum result in achieving good optical transparency and conductivity of the thin film. The CuGaO2 thin films were fabricated on quartz substrate via the Radio Frequency (RF) magnetron sputtering technique with varying substrate temperatures and different annealing temperatures. The p-type thin films were deposited at a temperature ranging from room temperature, 100°C, 200°C and 300°C. The samples were also annealed varying from temperature of 500°C, 600°C, 700°C and 800°C. The fabricated sample were characterized using X-ray diffraction (XRD), UV-Visible spectroscopy, and atomic force microscope (afm). XRD showed a peak at 2θ = 36.10° (012). The optical transparency values achieved from UV-Vis spectrometer were seen to be approximately 80% and the bandgaps were found to be in the range of 3.34-3.43 eV which is in line with the bandgap value from the research on CuGaO2 thin films.  From the afm, the mean surface roughness increases with increasing temperature and this is due to the increment of grain size. The highest grain size was observed at substrate temperature of 200°C.